Pengaruh Pendidikan Karakter Mahasiswa Terhadap Sikap Disiplin & Mandiri di Universitas Muhammadiyah Sidoarjo - Banna Nidham Ulhaq; Imam Fauji (Kuttab: Jurnal Ilmu Pendidikan Islam, 2025)
Abstract: This study aims to analyze the influence of character education on the attitude of discipline and independence of students at the University of Muhammadiyah Sidoarjo (UMSIDA). The study used a quantitative correlative approach with a random sampling technique, involving 300 new students as a sample from a total population of 2,145 students. Data collection was carried out through a questionnaire with a Likert scale, and the data were analyzed using simple linear regression techniques and correlation analysis. The results showed a strong positive correlation between character education and discipline (r = 0.627) and independence (r = 0.617). Regression analysis revealed that an increase in character education contributed to an increase in discipline by 63% and independence by 64.7%. These results prove the influence of the Student Character Education (PKMU) program managed by the Directorate of Al-Islam and Muhammadiyah UMSIDA in shaping student character, especially in the aspects of discipline and independence.